Physiochemical and electrical properties of refined, bleached and deodorized palm oil under high temperature ageing for application in transformers - Mohamad N.A.; Azis N.; Jasni J.; Kadir M.Z.A.A.; Yunus R.; Yaakub Z. (MDPI, 2023)
Bleaching; Cleaning; Dielectric properties; Electric properties; Fiber optic sensors; Petroleum refining; Potassium hydroxide; Thermal aging; Bleached; High temperature; Open condition; Physio-chemical; Refined; Palm oil